Warm Atlantic Water Explains Observed Sea Ice Melt Rates North of Svalbard. Issue 8 (12th August 2020) - Duarte, Pedro; Sundfjord, Arild; Meyer, Amelie; Hudson, Stephen R.; Spreen, Gunnar; Smedsrud, Lars H.
Abstract: Warm Atlantic water (AW) that flows northward along the Svalbard west coast is thought to transport enough heat to melt regional Arctic sea ice effectively. Despite this common assumption, quantitative requirements necessary for AW to directly melt sea ice fast enough under realistic winter conditions are still poorly constrained. Here we use meteorological data, satellite observations of sea ice concentration and drift, and model output to demonstrate that most of the sea ice entering the area over the Yermak Plateau melts within a few weeks. Simulations using the Los Alamos Sea Ice Model (CICE) in a 1‐D vertically resolved configuration under a relatively wide range of in situ observed atmospheric and ocean forcing show a good fit to observations. Simulations require high‐frequency atmospheric forcing data to accurately reproduce vertical heat fluxes between the ice or snow and the atmosphere. Moreover, we switched off hydrostatic equilibrium to properly reproduce ice and snow thickness when observations showed that ice had a negative freeboard, without surface flooding and snow‐ice formation. This modeling shows that realistic melt rates require a combination of warm near‐surface AW and storm‐induced ocean mixing. However, if AW is warmer than usual (>5°C), then lower mixing rates are sufficient. Our results suggest that increased winter storm frequency and increased heat content of the AW may work together in reducing future sea ice cover in the Eurasian basin. Plain Language Summary: Northwest of Svalbard, north of Norway, an area known as Whalers Bay stays ice‐free in winter despite the negative air temperatures. It has been assumed that this open water is maintained by inflow of warm Atlantic water (AW) along Svalbard's west coast; however, this mechanism has never been demonstrated quantitatively. We combine observations and results from modeling to calculate the rate of ice melting necessary to keep Whalers Bay ice‐free and the amount of heat that must be transferred from the ocean to the ice to sustain such melting. We conclude that the presence of AW combined with the occurrence of storms releases the amount of heat necessary to keep the area ice‐free. When the AW is close to the surface and its temperature is above about 5°C, storms are no longer necessary to enhance heat transfer and produce the required melting. Since the amount of heat transported by the AW and the storm frequency have been increasing over several decades, we expect that the ice‐free area will increase in the future, affecting air‐sea‐ice fluxes, water mass transformation, marine ecology, sea ice cover, and commercial activity including transportation and fishing. Key Points: Most of the sea ice entering the area known as Whalers Bay, in the NW of Svalbard, melts in less than a month, keeping it almost ice‐free Melting rates larger than 1.5 m month −1 result from a combination of the presence of warm Atlantic water and storm‐enhanced mixing In the absence of storms, estimated high sea ice melting rates require ocean surface temperature above 5°C